A study on the factors that can influence employee’s performance among government servants at Bangunan Persekutuan Batu Pahat / Nur Fareha Isa - Isa, Nur Fareha (2014)
Employee is an important asset in the organization. The success and failure of the organization depends on the employee performance. This paper aims to study on the factors that can influence employee’s performance among government servants at Bangunan Persekutuan Batu Pahat. The independent variables that involved in this study are of compensation, working environment and career development. For these project paper purposes, 110 questionnaires were distributed. However, only 100 of the respondent well managed to return back the questionnaire. Simple random sampling is used where the all the employees at Bangunan Persekutuan has an equal chance of being chosen as the respondent. There have three objectives on this study. First objective is to determine the relationship between compensation, working environment and career development with employee’s performance. Second objective is to identify the most factor that influence employee’s performance. Last objective is to measure the level of each factor that influence employee’s performance. The researcher have used SPSS program version 21.0 where the researcher have used reliability analysis, frequency analysis, descriptive analysis, correlation and regression analysis. In the end of this paper, the researchers have provided several recommendations regarding the factors that can influence employee’s performance.